(untitled) (Journal of Computational Mathematics, 2021)
In this paper, we investigate the optimality conditions of a class of special nonsmooth programming F(x)=_i=1^m|{f_i(x),c_i}| which arises from L_1-norm optimization, where c_iR is constant and f_iC^1,i=1,2,…,m. These conditions can easily be tested by computer.